Lateral Response of a Single Pile under Combined Axial and Lateral Cyclic Loading in Sandy Soil - Kahribt, Muqdad Abdallah; Abbas, Jasim M. (Salehan Institute of Higher Education, 2018)
According to practical situation, there have been limited investigations on the response of piles subjected to combined loadings especially when subjected to cyclic lateral loads. Those few studies led to contradictory results with regard to the effects of vertical loads on the lateral response of piles. Therefore, a series of experimental investigation into piles in dense sand subjected to combination of static vertical and cyclic lateral loading were conducted with instrumented model piles. The effect of the slenderness ratio (L/D) was also considered in this study (i.e. L/D= 25 and 40). In addition, a variety of two-way cyclic lateral loading conditions were applied to model piles using a mechanical loading system. One hundred cycles were used in each test to represent environmental loading such as offshore structures. It was found that under combined vertical and cyclic lateral loads the lateral displacement of piles decreased with an increase in vertical load whereas it causes large vertical displacements at all slenderness ratios. In addition, for all loading conditions the lateral, vertical (settlement and upward) displacements and bending moments increased as either the magnitude of cyclic load or the number of cycles increases.Â